Current advances, research needs and gaps in mycotoxins biomonitoring under the HBM4EU - Alvito, Paula (2022)
Funding Information: Thanks are due to CESAM (UIDP/50017/2020+UIDB/50017/2020+LA/P/0094/2020), and ToxOmics (UIDB/00009/2020; UIDP/00009/2020), through national funds. L.B. thanks Research Infrastructure RECETOX RI (No. LM2018121), financed by the Ministry of Education, Youth and Sports, and the project CETOCOEN EXCELLENCE (No. CZ.02.1.01/0.0/0.0/17_043/0009632) for a supportive background of the European Union’s Horizon 2020 research and innovation program under grant agreement No. 857560, and to the HBM4EU, under grant agreement No. 733032. This publication reflects only the authors’ view and the European Commission is not responsible for any use that may be made of the information it contains. Funding Information: This study was co-funded by the HBM4EU, which has received funding from the European Union’s research and innovation programme Horizon 2020 under grant agreement No. 733032, and from the authors’ institutions. Publisher Copyright: © 2022 by the authors.